The BRICS in the Contemporary Global Order: Objectives, Capabilities, and Limitations - Alberto Hoyos Varela; Rafael Gustavo Miranda Delgado (Otoritas : Jurnal Ilmu Pemerintahan, 2019)
For the first time in the history of mankind several powers emerge simultaneously in different latitudes and can interact intensively. The Contemporary Global Order has presented significant changes among which highlight the absolute and relative decline of American power, and the emergence of new actors who have greater agency power in their international relations. One of these actors is the so-called BRICS that brings together Brazil, Russia, India, China and South Africa. For this reason the aim of this investigation is to analyzing the effective and potential power of the BRICS in the Contemporary Global Order. The methodology is it is situated inside the analytical eclecticism which is characterized by explaining a certain phenomenon without using a block of explanations sustained in a single tradition, but it takes and re-means the elements that it considers most pertinent for the case study. The article states that the BRICS do not claim or have the capacity to become hegemons. The objectives and capabilities of the BRICS have been especially notable in terms of international political economy, especially in the financial architecture, where China has its greatest power. The BRICS can promote an alternative to the existing game rules in the international system and promote a more plural world. They have the capacity to reform and build international economic institutions that allow a fairer distribution of material resources. They can curb unilateral global power interventions in regional affairs, framing interventions for humanitarian causes within multilateralism and the Responsibility to Protect. In terms of democracy and human rights, they will not make any contribution since their main actors, such as China and Russia, are examples of disrespect for these values.